Prospective Physics and Science Teachers' Mental Models about the Concept of Work - Ayşegül Sağlam-Arslan; Işık Saliha Karal; Hava İpek Akbulut (Universitas Pendidikan Indonesia, 2020)
Work, as a concept, is often encountered in daily life, but the meaning of work in physics is closely related to power, force, and energy. Studies made about various concepts and subjects have proved that using words in ways different from their scientific meanings has a negative effect on teaching, and causes conceptual complexities and/or generation of alternative mental models. This study aimed to determine the mental models of prospective physics and science teachers about the concept of work. This study was conducted with the participation of 107 prospective teachers in the Physics and Science Teacher Training program. The trainee teachers' understandings were determined by using an achievement test, consisting of three open-ended questions, developed by the researchers. Data obtained were first analyzed according to the level of understanding demonstrated, and then the mental models were determined by using these levels. Four types of mental models about work were identified, specifically the scientific,, the scientific synthesis, the initial synthesis, and the initial models. The synthesis model is the dominant mental model, and it has been developed by prospective teachers from two disciplines.